ANALISIS DEEP DAN SURFACE APPROACH SISWA SEKOLAH DASAR DALAM PEMBELAJARAN MATEMATIKA DENGAN MODEL PROBLEM-BASED LEARNING (PBL) BERBANTUAN PIZZA - Ni Kadek Vingki Aryanti; Ni Komang Listyawati (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
ABSTRACT Implementing the Deep Learning Approach in elementary mathematics education requires instructional strategies that not only improve learning outcomes but also foster meaningful ways of understanding mathematical concepts. Although Problem-Based Learning (PBL) has been widely investigated, evidence regarding its influence on students' learning approaches, particularly deep approach and surface approach, remains limited. This study aimed to examine changes in students' learning approaches after participating in fraction instruction using PBL supported by pizza media. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed, involving 31 fourth-grade students from SDN 11 Kesiman, Denpasar. Data were collected using the Revised Two-Factor Study Process Questionnaire (R-SPQ-2F) and analyzed through descriptive and inferential statistics. The findings revealed that PBL assisted by pizza media significantly enhanced students' deep approach (p < 0.001) with a very large effect size (Cohen's d = 1.56), whereas changes in the surface approach were not statistically significant. These findings indicate that PBL supported by pizza media is more effective in promoting students' conceptual understanding than in changing surface-oriented learning tendencies. Furthermore, the study demonstrates that changes in students' learning approaches can serve as an alternative indicator for evaluating the implementation of the Deep Learning Approach in elementary mathematics instruction. ABSTRAK Implementasi Pendekatan Deep Learning pada pembelajaran matematika sekolah dasar memerlukan strategi yang tidak hanya meningkatkan hasil belajar, tetapi juga membentuk cara siswa memahami konsep secara lebih bermakna. Meskipun Problem-Based Learning (PBL) telah banyak diteliti, bukti mengenai pengaruhnya terhadap learning approach siswa, khususnya deep approach dan surface approach, masih terbatas. Penelitian ini bertujuan mengeksplorasi perubahan pendekatan belajar siswa setelah mengikuti pembelajaran materi pecahan menggunakan PBL berbantuan media pizza. Penelitian menggunakan pendekatan kuantitatif dengan desain pre-experimental one-group pretest–posttest yang melibatkan 31 siswa kelas IV SDN 11 Kesiman, Denpasar. Data dikumpulkan menggunakan Revised Two-Factor Study Process Questionnaire (R-SPQ-2F) dan dianalisis melalui statistik deskriptif serta inferensial. Hasil penelitian menunjukkan bahwa penerapan PBL berbantuan media pizza meningkatkan deep approach secara signifikan (p < 0,001) dengan effect size yang sangat besar (Cohen's d = 1,56), sedangkan perubahan pada surface approach tidak signifikan. Temuan ini menunjukkan bahwa PBL berbantuan media pizza lebih efektif dalam mendorong siswa membangun pemahaman konseptual dibandingkan sekadar mengubah kecenderungan belajar permukaan. Penelitian ini juga memperlihatkan bahwa perubahan learning approach dapat digunakan sebagai indikator untuk mengevaluasi implementasi Pendekatan Deep Learning pada pembelajaran matematika di sekolah dasar.